(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
These reports are quite different from one another in terms of both the substance and themanner of the disclosures, which makes it difficult to compare them. Inter-rater reliability has beentaken into consideration nonetheless, the likelihood of slight discrepancies in assigning the weights topieces of HR information cannot be ruled out, despite attempts to reduce these mistakes. This isdespite the fact that these inaccuracies have been kept to a minimum. Throughout the course of ourinquiry, we have adhered to both the quantitative and the subjective schools of thought. Within thescope of this inquiry, a contextual analysis technique has been obtained.